Importance Performance Analysis Pelayanan Farmasi Klinik di RS Universitas Sumatera Utara dalam Persepsi Perawat - Rima Elfitra Rambe; Khairunnisa Khairunnisa; Wiryanto Wiryanto (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2023)
Clinical Pharmacy Services (CPS) is provided by clinical pharmacists as members of the healthcare team. This is beneficial for hospital care. Therefore, knowing nurses' perception of CPS can determine the quality of healthcare provided and help in its improvement. This study aims to determine nurses' perception of clinical pharmacy services at the Universitas Sumatera Utara hospital, Medan, Indonesia. This is a descriptive study that used the Importance–Performance Analysis (IPA) method. The data were obtained by interviews and questionnaires to 60 nurses from October-December 2021. Five clinical pharmacy services are patient drug history, reconciliation, drug information services, recommendations and intervention in the integrated medical record, and sterile product dispensing. This study found that nurses have experienced the five clinical pharmacy services for as many as 52-60 people (87%-100%). Reconciliation, recommendations, and intervention in the integrated medical record are in Quadrant I.        It shows that the performance of these services has not met the nurses' expectations. Drug information services are in Quadrant II. It shows that the service performance has been in line with the expectations. The patient's drug history is in Quadrant III. It shows low performance and is not expected by the nurse. The sterile product dispensing by clinical pharmacists is in quadrant IV. It shows that even though the perceived performance is good, the respondents do not consider this service to be important.